Review of Thoracic Causes of Systemic Arterial Air Embolism on Computed Tomography. Issue 3 (May 2020) - Kramer, Michael; Parekh, Maansi; Modi, Roshan Y.; Donuru, Achala
Abstract : Systemic arterial air embolism (SAAE) is a rare but potentially life-threatening condition that may occur when air enters into pulmonary veins or directly into the systemic circulation after pulmonary procedures (biopsy or resection) or penetrating trauma to the lung. While venous air embolism is commonly reported, arterial air embolism is rare. Even a minor injury to the chest along with positive-pressure ventilation can cause SAAE. Small amounts of air may cause neurological or cardiac symptoms depending on the affected arteries, while massive embolism can result in fatal cardiovascular collapse. We discuss the various causes of SAAE, including trauma, computed tomography–guided lung biopsy, and various intervention procedures such as mechanical circulatory support device implantation, coronary catheterization, and atrial fibrillation repair. SAAE diagnosis can be overlooked because its symptoms are not specific, and confirmation of the presence of air in the arterial system is difficult. Although computed tomography is the optimal imaging tool for diagnosis, patient instability and resuscitation often precludes its use. When imaging is performed, awareness of the causes of SAAE allows the radiologist to promptly diagnose the condition and relay findings to the clinicians so that treatment, namely hyperbaric oxygen therapy, may be started promptly. Abstract : Supplemental Digital Content is available in the text.